2023
DOI: 10.3390/ijms24043739
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria-Targeted Antioxidants, an Innovative Class of Antioxidant Compounds for Neurodegenerative Diseases: Perspectives and Limitations

Abstract: Neurodegenerative diseases comprise a wide spectrum of pathologies characterized by progressive loss of neuronal functions and structures. Despite having different genetic backgrounds and etiology, in recent years, many studies have highlighted a point of convergence in the mechanisms leading to neurodegeneration: mitochondrial dysfunction and oxidative stress have been observed in different pathologies, and their detrimental effects on neurons contribute to the exacerbation of the pathological phenotype at va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 167 publications
0
14
0
Order By: Relevance
“…However, clinical trials using non-mitochondria-targeted antioxidants have shown that non-mitochondria-targeted antioxidant therapies are not effective in the treatment of aging and age-related diseases [ 154 , 155 ]. To complement these clinical findings, mitochondria-targeting antioxidants have recently been applied to various animal models, and there is growing evidence that mitochondria-targeting antioxidants have beneficial effects on aging and age-related diseases [ 156 , 157 ]. Therefore, research on how to effectively deliver genetic and pharmacological therapeutics targeting mitochondria will provide good therapeutic clues to break the vicious cycle leading to aging and age-related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical trials using non-mitochondria-targeted antioxidants have shown that non-mitochondria-targeted antioxidant therapies are not effective in the treatment of aging and age-related diseases [ 154 , 155 ]. To complement these clinical findings, mitochondria-targeting antioxidants have recently been applied to various animal models, and there is growing evidence that mitochondria-targeting antioxidants have beneficial effects on aging and age-related diseases [ 156 , 157 ]. Therefore, research on how to effectively deliver genetic and pharmacological therapeutics targeting mitochondria will provide good therapeutic clues to break the vicious cycle leading to aging and age-related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…This may rely, at least partially, on the dual role of ROS, implying that in addition to their implication in neurodegeneration, some oxidant species, such as superoxide and hydrogen peroxide (O 2 2− and H 2 O 2 ) function as signaling molecules of essential redoxdependent signaling pathways [101]. Thus, antioxidants that directly target mitochondria seem to represent a more efficient approach to attenuating local ROS production, and some of these compounds have already led to promising results in clinical trials [102].…”
Section: Oxidative Stress and Mitochondrial Dysfunctionmentioning
confidence: 99%
“…A growing body of studies suggests that by neutralizing harmful free radicals, antioxidants prevent oxidative damage to cells and tissues, which are implicated in developing chronic diseases. Antioxidants play a crucial role in reducing the risk of chronic liver diseases [13], chronic heart failure [14], neurodegenerative diseases [15,16], and chronic kidney disease [17]. It has also been shown that antioxidants can reduce cardiotoxicity induced by anticancer therapy [18].…”
Section: Antioxidants Reduce the Risk Of Chronic Diseasesmentioning
confidence: 99%